Improving Engineering Students' Learning Outcomes through Strategies Learning Start with a Question - Setiawan, Doni; Faoziyah, Nina (Lembaga Penelitian dan Pendidikan Mandala, 2025)
This study began with a situation where the teaching of Basic Physics to Engineering students, Universitas Muhammadiyah Tegal was carried out using a monotonous lecture method, making it difficult for students to understand the material presented. The problem identified in this study is how to describe the improvement in learning outcomes of Engineering students through the application of the Learning Start with a Question strategy. The purpose of this study was to improve the learning outcomes of basic Physics of engineering students by implementing the Learning Start with a Question strategy. This study is a type of classroom action research, with 16 Engineering students in semester 2 as research subjects. The instruments used included learning achievement tests and observation sheets. The indicator of success was determined by achieving a minimum of 75% of students achieving a score of at least 65, which received a good score. The results of the study showed that in cycle I, 7 students or 43.7% had achieved completeness, in cycle II as many as 11 students or 68.7%, and in cycle III as many as 14 students or 87.5% had achieved completeness. The conclusion of this study is that the application of the Learning Start with a Question strategy can improve the learning of basic Physics of Engineering students.